Fatigue at enrollment predicts EDSS worsening in the New York State Multiple Sclerosis Consortium. (January 2020) - Vaughn, Caila B; Kavak, Katelyn S; Dwyer, Michael G; Bushra, Aisha; Nadeem, Muhammad; Cookfair, Diane L; Ramanathan, Murali; Benedict, Ralph HB; Zivadinov, Robert; Goodman, Andrew; Krupp, Lauren; Motl, Robert W; et al.
Background: Fatigue is one of the most common and distressing symptoms among persons with multiple sclerosis (pwMS). Objective: The aim of this study is to evaluate fatigue as a predictor for disease worsening among pwMS. Methods: In this retrospective cohort study of New York State MS Consortium (NYSMSC) registry, MS patients reporting moderate-to-severe fatigue at study enrollment ( n = 2714) were frequency matched to less-fatigued subjects ( n = 2714) on age, baseline Kurtzke Expanded Disability Status Scale (EDSS), disease duration, and MS phenotype. Change from baseline patient-reported outcomes (PROs), as measured by LIFEware ™, categorized participants into two groups: those with stable/improved outcomes and those who worsened. In a subgroup of patients with longitudinal data ( n = 1951), sustained EDSS worsening was analyzed using Cox proportional hazards modeling to explore the effect of fatigue. Results: The median survival time from study enrollment to sustained EDSS worsening was 8.7 years (CI: 7.2–10.1). Participants who reported fatigue at baseline were more likely to experience sustained EDSS worsening during follow-up (HR: 1.4, 95% CI: 1.2–1.7). Patients who were fatigued at baseline were also more likely to report worsening psychosocial limitations (all p s ⩽ 0.01). Conclusion: In addition to being a common symptom of MS, severe fatigue was a significant predictor for EDSS worsening in the NYSMSC.